Stable integral simplicial volume of 3‐manifolds. Issue 2 (10th May 2021) - Fauser, Daniel; Löh, Clara; Moraschini, Marco; Quintanilha, José Pedro
Abstract: We show that non‐elliptic prime 3‐manifolds satisfy integral approximation for the simplicial volume, that is, that their simplicial volume equals the stable integral simplicial volume. The proof makes use of integral foliated simplicial volume and tools from ergodic theory.